Politik hukum sebagai arah dan kebijakan negara - 29, diah kumala (Maliki Interdisciplinary Journal, 2026)
Legal policy plays a fundamental role in determining the direction of national legal development in Indonesia. Legal policy serves as the foundation for the state in forming, replacing, and developing a legal system oriented towards the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. Through legal policy, legal policies are formulated in a planned manner to ensure legal certainty, justice, protection of human rights, and the welfare of the people. The pillars of national law, such as the rule of law, people's sovereignty, responsible government, and the presidential system, form the basis for state administration and the development of legislation. However, strengthening the legal system still faces challenges in the form of legal pluralism, weak law enforcement, regulatory disharmony, and a low legal culture among the people, which need to be addressed seriously and continuously. In the context of national development, legal policy functions as a strategic instrument that directs development implementation through planning documents such as the RPJPN, RPJMN, and RKP to achieve national goals in a measurable and consistent manner. Thus, legal policy and national development are intertwined, where legal policy directs legislation to support development goals, while the dynamics of development form the basis for legal policy changes that are more adaptive and responsive to the needs of society